Role of Runx2 in Calcific Aortic Valve Disease in Mouse Models - Dharmarajan, Subramanian; Speer, Mei Y.; Pierce, Kate; Lally, Jake; Leaf, Elizabeth M.; Lin, Mu-En; Scatena, Marta; Giachelli, Cecilia M. (Frontiers in Cardiovascular Medicine, 2021)
Background (CAVD is common in the aging population and characterized by histological changes of the aortic valves including extracellular matrix remodeling, osteochondrogenic differentiation and calcification. Combined, these changes lead to aortic sclerosis, aortic stenosis and eventually to heart failure. Runx2 is a transcription factor highly expressed in the calcified aortic valves. However, its definitive role in the progression of CAVD has not been determined. In this study, we utilized constitutive and transient conditional knockout mouse models to assess the molecular, histological, and functional changes in the aortic valve due to Runx2 depletion. Methods Lineage tracing studies were performed to determine the provenance of cells giving rise to Runx2+ osteochondrogenic cells in the aortic valves of LDLr-/- mice. Hyperlipidemic mice with constitutive or temporal depletion of Runx2 in valvular interstitial cells (VICs) and sinus wall cells were further investigated. Following feeding with a diabetogenic diet, mice were examined for changes in gene expression, blood flow dynamics, calcification, and histology. Results SM22α+ VICs and sinus wall cells gave rise to Runx2+ osteochondrogenic cells in diseased mouse aortic valve. Conditional depletion of Runx2 in SM22+ VICs and sinus wall cells led to decreased osteochondrogenic gene expression in diabetic LDLr-/- mice. Transient conditional depletion of Runx2 in SMA+ VICs and sinus wall cells of the LDLr-/-ApoB100 CAVD mouse early in disease led to a significant reduction in aortic peak velocity, mean velocity, and mean gradient, suggesting a causal role of Runx2 on the progression of AS. Finally, leaflet hinge and sinus wall calcification were significantly decreased in the aortic valve following conditional and temporal Runx2 depletion, but no significant effect on valve cusp calcification or thickness were observed. Conclusions Runx2 was expressed early in aortic valve disease, and was required for osteochondrogenic differentiation of VICs and sinus wall cells. Transient depletion of Runx2 in VICs and sinus wall cells in a mouse model of CAVD with high prevalence of hemodynamic valve dysfunction led to improved aortic valve function. Furthermore, leaflet hinge and sinus wall calcification, even in the absence of significant leaflet cusp calcification, may be sufficient to cause significant valve dysfunction in mice.